2021
DOI: 10.1021/acsfoodscitech.1c00009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Gelling Properties of Duckweed Protein Concentrate

Abstract: An isolation procedure for proteins from duckweed was optimized based on a previously developed method for protein isolation from sugar beet leaves. Optimization included the protocol for disrupting cells and protein recovery. With the optimized protocol, protein was isolated (protein yield 14.2%, RuBisCO yield 27%). The concentrate was off-white and contained 67.2% protein. The isolation procedure resulted in a large enrichment in RuBisCO (from 48% to 92%). Denaturation of duckweed protein concentrate was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…Moreover, Nasir et al [ 35 ] found a low Mw of shortfin scad muscle protein hydrolysate (SSMPH), with high potential bioactivity and functional properties particular to SSMPH peptides (<3 kDa) that exhibited the highest ACE inhibitory activity and DPPH scavenging activity. In addition, Nieuwland et al [ 36 ] reported that high concentrations of glutamic acid, arginine and glycine are conditionally essential amino acids in the human diet. Therefore, consumption of the PE and PCH could assist people who suffer from limited synthesis of these amino acids due to pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Nasir et al [ 35 ] found a low Mw of shortfin scad muscle protein hydrolysate (SSMPH), with high potential bioactivity and functional properties particular to SSMPH peptides (<3 kDa) that exhibited the highest ACE inhibitory activity and DPPH scavenging activity. In addition, Nieuwland et al [ 36 ] reported that high concentrations of glutamic acid, arginine and glycine are conditionally essential amino acids in the human diet. Therefore, consumption of the PE and PCH could assist people who suffer from limited synthesis of these amino acids due to pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RuBisCo from duckweed have gelation properties comparable with egg white protein and better than soy protein. 15 With regard to the microstructure observed with confocal laser scanning microscopy, RuBisCo gel density is correlated to the protein concentration. Furthermore, an increase in gel network coarseness is observed upon NaCl addition to the gel system at 5% protein concentration resulting in lower gel strength.…”
Section: Solubility Of Proteinsmentioning
confidence: 99%
“…The minimum solubility is observed at pH 3.5–5 (∼10% soluble), which correlates to RuBisCo having a isoelectric point around pH 4.5 . The solubility is slightly higher at pH 2 and increases from pH 5 to a maximum of ∼80% at pH 10. ,,,, Using a pH-shift method where the protein concentrate is solubilized at pH 11 or 12 prior to readjustment to pH 7 increases the protein solubility at pH 7, but the alkaline pH also induce formation of protein cross-linking products, lanthionine, and lysinoalanine, which lowers the content of the essential amino acids, cysteine, and lysine and lowers the protein digestibility and may as well change other functional properties. Similarly, the solubility of leaf protein from perennial ryegrass was improved by solubilizing at alkaline pH before readjusting to neutral pH …”
Section: Functionalityleaf Protein In Food Applicationsmentioning
confidence: 99%
See 2 more Smart Citations